Managing Request-Offer Negotiations Under the GATS The Case of Legal Services - Geloso Grosso, Massimo (OECD Publishing, 2004)
This study forms part of on-going OECD work on trade in services, in co-operation with UNCTAD, aimed at assisting WTO Members in managing request-offer negotiations under the GATS. The key objective is to help officials of WTO Members in both gaining a greater insight into the particular issues of importance in the legal services sector and how they might be approached in the negotiations. While only modest liberalisation of legal services trade was achieved during the Uruguay Round, the current negotiations offer the opportunity to achieve greater levels of liberalisation, which may lead to significant economic benefits to all countries. In addition, the peculiar characteristic of legal services is that the potential downsides stemming from liberalisation - both in terms of market failures to achieve social objectives and of the displacement of local suppliers - are likely to be less significant in these services
Keywords: Trade